Quality of life of women after mastectomy - Konieczny, Magdalena (Journal of Education, Health and Sport, 2022)
Introduction. The occurrence of breast cancer in a woman is a crisis event that requires the implementation of long-term and burdensome treatment. The quality of life of women in such a situation is changing. For this reason, it is very important to assess the mental condition, emotional state of women and the degree of their acceptance of the new situation, as well as to recognize the expectations and needs of breast cancer patients. The goal of the work was the assessment of the quality of life of women with diagnosed breast cancer who underwent mastectomy. Material and methods. The study was conducted at the Podkarpackie Oncology Center in Brzozów among 231 women with breast cancer, in whomwho were treated with surgery (mastectomy). The research was carried out by means of a diagnostic survey using the proprietary questionnaire consisting of 39 questions. The research was approved by the Hospital Director and the Bioethics Committee. Results. The emotional state of the respondents was assessed as bad (26.9%) or rather bad (21.3%), and one third of the respondents felt sad and apathy (very often - 26.9%; daily - 6.8%). Women most often feared tumor metastasis (47.2%), disease recurrence (33.3%) and pain (29.0%). As limitations in everyday life resulting from the disease, the majority of women considered disruptions in family life and social life (38.3) as well as reduced work efficiency (30.6%). Conclusions. Women had a reduced quality of life, especially in the emotional, family and professional spheres. Respondents with breast cancer expect greater support from the doctor, which may constitute the basis for introducing changes in the education of medical students and conducting postgraduate training in this field.